Pengaruh Model Sugesti – Imajinasi dengan Media Lagu Bunda terhadap Kemampuan Menulis Cerpen Siswa Kelas XI SMK Swasta YPK Medan - Dwi Oktaviani; Nila Safina; Ratna Soraya (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2021)
This study aims to describe the ability to write short stories using the Suggestion-Imagination learning model with the media song of class XI students of YPK Private Vocational School Medan, to describe the ability to write short stories using the Suggestion-Imagination learning model with video media for class XI students at YPK Private Vocational School Medan, To describe whether there is a significant effect on the ability to write short stories using the Suggestion-Imagination learning model with the media of song for class XI students of YPK Private Vocational School Medan. The sample in this study was 60 students. From the results of data processing, the average value of the experimental class was 71.6 while the control class was 65.5. Thus it can be said that the results of learning to write short stories in the experimental class are higher than the control class. After testing the hypothesis, the value of tcount = 3.144 was then adjusted to ttable at a significant level of = 5% with dk = (n1+n2) – 2 = (30+30 – 2) = 58, then obtained a significant level of 5% = 2.002 ( by interpolation). Then compared between tcount and ttable, it was obtained tcount 3.144 > ttable 2.002 so that Ho (Nil Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted.